Digesting in hypoxia: impact on gastric evacuation rate and postprandial metabolism (SDA) of Atlantic cod, Gadus morhua ... - Chabot, Denis; Behrens, Jane; Andersen, Niels (ASC 2015 - Theme session R, 2024)
No abstracts are to be cited without prior reference to the author.Chronic hypoxia reduces both food consumption and growth rate of ﬁsh. As digestion results in increased oxygen uptake, the so?called speciﬁc dynamic action (SDA), a possible mechanism is that the reduction of aerobic metabolic scope imposed by hypoxia limits the increase in oxygen uptake during hypoxia. This in turn prolongs the SDA response and, conversely, decreases ingestion rate over time. However, nothing is known of the underlying processes in the stomach and the gut. This study investigates gastric evacuation (GE) rates at 3 levels of dissolved oxygen (90, 55 and 40% sat.) and the SDA response in normoxia and hypoxia (40 % sat.). GE proceeded signiﬁcantly slower at 55 and 40% sat. compared with normoxia, and, as digestion proceeded, the moisture content of the bolus increased more slowly at 55 and 40% sat. than in normoxia. Further analysis of the available SDA data will reveal to what extent these support the suppressing eﬀects of ...